A LASER GC-IRMS TECHNIQUE FOR IN SITU STABLE ISOTOPE ANALYSES OF CARBONATES AND PHOSPHATES - Sharp Z.D.; Cerling T.E. (My University, 1996)
A technique is described whereby in situ carbon and oxygen isotope analyses of carbonates and organic phosphates can be made with the use of a CO2 laser. The CO2 gas generated by thermal decarbonation from the laser is entrained in a helium carrier gas, passes through a chromatographic column (GC), and is admitted directly into the isotope ratio mass spectrometer (IRMS). No vacuum systems, pumps, or cryogenic traps are used. All carbonates and biogenic phosphates can be analyzed, no special sample preparation is required and analyses can be made every 3 minutes. The use of a helium carrier gas allows for extremely small samples to be analyzed and the GC column effectively separates CO2 from any other potential contaminating gases (e.g., SO2 which is a particular problem in organic apatite). The average reproducibility of calcite, dolomite, magnesite, rhodochrosite, siderite, and smithsonite (ZnCO3), is 0.29%% for oxygen and 0.19%% for carbon (1σ); the most ?homogeneous? samples are reproducible to better than 0.1%% for carbon and 0.2%% for oxygen. The difference between the laser and conventional values for carbon isotope ratios [Δ13C(laser-conv)] is 0.05 +/- 0.30%% for all carbonates (excluding siderite). The Δ18O(laser-conv) value varies from carbonate to carbonate and may be related to the electronegativities of the cations, grain size (or crystallinity), formation of CO and O2, and reaction with included organic matter. For calcite and rhodochrosite, the Δ18O(laser-conv) value is 0.3 +/- 0.4%%; for siderite, magnesite, and dolomite, the Δ18O(laser-conv) value is 1.7 +/- 0.3%%. The δ13C values of tooth enamel are the same as those obtained by conventional acid digestion. The laser δ18O values are equal to the δ18O values of the phosphate, and approx. 7%% lighter than the ?carbonate? oxygen. The carbonate group in the apatite (equiv. 7.6% oxygen) exchanges with the (PO=4)-bound oxygen to produce CO2 with a δ18O equal to the phosphate oxygen. The laser technique provides a rapid alternative to the difficult phosphate extraction technique for oxygen isotope measurements in tooth enamel.